2021
DOI: 10.1029/2020jc016731
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale Phenomena Due to the Brazil Current Crossing of the Vitória‐Trindade Ridge

Abstract: At latitudes north of which it becomes a robust western boundary current, the newly formed, poleward-flowing Brazil Current (BC) encounters a zonal seamount chain-the Vitória-Trindade Ridge (VTR). Located at 20.5°S, with seamounts reaching up to 30 m below the surface, the VTR poses an obstacle for the typically 150-m-deep BC southward path (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 80 publications
(200 reference statements)
3
12
0
Order By: Relevance
“…(2016) from the analysis of 13 years of ADCP data in the Drake Passage. The departure from the QG regime observed during winter and early spring is consistent with reports of increased submesoscale activity in numerical simulations at this period (e.g., Callies et al., 2015; Napolitano et al., 2021; Rocha, Chereskin, et al., 2016; Sasaki et al., 2014), being also detected in altimetry data (Dufau et al., 2016; Vergara et al., 2019) and by in situ observations (Callies et al., 2015). In winter, when the mixed layer is deep and stratification is weak, there is more available potential energy and the EKE produced by mixed‐layer instabilities is higher than in summer, when the opposite occurs (Callies et al., 2015).…”
Section: The Surface Kinetic Energy Spectra In the South Atlanticsupporting
confidence: 90%
See 2 more Smart Citations
“…(2016) from the analysis of 13 years of ADCP data in the Drake Passage. The departure from the QG regime observed during winter and early spring is consistent with reports of increased submesoscale activity in numerical simulations at this period (e.g., Callies et al., 2015; Napolitano et al., 2021; Rocha, Chereskin, et al., 2016; Sasaki et al., 2014), being also detected in altimetry data (Dufau et al., 2016; Vergara et al., 2019) and by in situ observations (Callies et al., 2015). In winter, when the mixed layer is deep and stratification is weak, there is more available potential energy and the EKE produced by mixed‐layer instabilities is higher than in summer, when the opposite occurs (Callies et al., 2015).…”
Section: The Surface Kinetic Energy Spectra In the South Atlanticsupporting
confidence: 90%
“…In winter, when the mixed layer is deep and stratification is weak, there is more available potential energy and the EKE produced by mixed‐layer instabilities is higher than in summer, when the opposite occurs (Callies et al., 2015). The seasonal cycle of the mixed layer thus affect the KE and consequently the spectral slopes, and it may be altered (not exclusively) by the presence of submesoscale instabilities (e.g., Sasaki et al., 2014), inertia‐gravity waves (e.g., Rocha, Chereskin, et al., 2016), and flow‐topography interactions (e.g., Napolitano et al., 2021). For more details in the seasonality of KE spectra, see Uchida et al.…”
Section: The Surface Kinetic Energy Spectra In the South Atlanticmentioning
confidence: 99%
See 1 more Smart Citation
“…Low PV values are prone to instabilities (D'Asaro et al, 2011;Thomas et al, 2008Thomas et al, , 2013. Here, we evaluate the two-dimensional PV (e.g., Lazaneo et al, 2020;Napolitano et al, 2021;Ramachandran et al, 2018;Thomas et al, 2016) from the objectively mapped field. If one assumes that the features are indeed SCVs and that the sampling of the SCV currents and density occurs through their centers, then an approximation of the Ertel PV is possible.…”
Section: The Scv Vertical Structurementioning
confidence: 99%
“…Transformation of PV is key in setting the dynamics of the EUC in the Gulf of Guinea. Due to the presence of the islands and topography, both friction and diapycnal mixing must play a prominent role, since flow-topography interactions are known to induce strong mixing (e.g., Lueck & Mudge, 1997;Naveira Garabato et al, 2004) and introduce PV anomalies (e.g., Gula et al, 2019;Napolitano et al, 2020;Wenegrat et al, 2018). Assene et al (2020) showed that isopycnal mixing also takes place during the rearranging of PV anomalies into eddies.…”
Section: Pv Anomalies In the Eucmentioning
confidence: 99%